Perjumpaan Pasar dan Dakwah: Ekspresi Kesalehan Anak Muda dan Komodifikasi Agama di Muslim United Yogyakarta - Hofizal Wadi; Roy Bagaskara (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2022)
The new religious movement is caused by a value crisis among young people, which results in alienation and contributes to the current spiritual crisis. The emergence of Islam United as a response to this problem with a new face, namely the millennial face in accordance with the needs of young people and the recurring trend of migration. Utilizing young people as a marketplace for various goods and ideologies is most profitable. In this phase, according to developmental theory, people are frequently confronted with a psychological crisis, including anxiety about the future, spirituality, success, mate, and others. This study employs ethnographic descriptive qualitative research methods. The Observatory Participant is a tool used by researchers to gather information by involving the social community members directly. Yogyakarta represents the new face of the religious movement and social piety of young people in urban areas, which is Muslim United. This religious movement is not only focused on increasing religiosity, but also profit-oriented with concrete activities in the form of religious studies, such as the Satnight study and the Sunrise study, which investigate aqidah, fiqh, hadith science, and the history of prophethood. Then the most important and urgent issue is commodification. The commodification of religion has become a crucial topic of discussion for altering the religiosity of Muslim United youths. In addition to studying, Muslim United youth alter their appearance by consuming the organization's religious products. After completing the study, they select the most suitable Islamic products, beginning with Rumah Warna merchandise owned by Muslim United, such as skullcaps, t-shirts, hats, hoodie jackets, scarves, waistbags, books, neck pillows, tumbler bikes, joggers, backpacks, and others